Do payers value rarity? An analysis of the relationship between disease rarity and orphan drug prices in Europe - Goran Medic; Daria Korchagina; Katherine Eve Young; Mondher Toumi; Maarten Jacobus Postma; Micheline Wille; Michiel Hemels (Taylor & Francis Group, 2017)
Background and Objective: Orphan drugs have been a highlight of discussions due to their higher prices than non-orphan drugs. There is currently no European consensus on the method of value assessment for orphan drugs. This study assessed the relationship between the prevalence of rare diseases and the annual treatment cost of orphan drugs in France, Germany, Italy, Norway, Spain, Sweden, and UK. Methods: Approved orphan drugs and prevalence data were extracted from the European Medicines Agency website. Annual treatment costs were calculated using ex-factory price. Simple regression was used to analyse the relationship between costs and prevalence. A specific bivariate analysis was performed for the rarest diseases (≤1 per 10,000). Results: 120 drugs were analysed. Prevalence ranged from 0.001 to 5 per 10,000 (mean 1.24, median 1). Annual treatment costs per patient ranged from €755 to €1,051,956 (mean €100,000, median €39,303). Results show a statistically significant inverse correlation between annual treatment cost and disease prevalence in all countries (France: r = −0.370, p = 0.002; Germany: r = −0.365, p = 0.002; Italy: r = −0.340, p = 0.002; Spain: r = −0.316, p = 0.041; UK: r = −0.358, p = 0.0004; Sweden: r = −0.414, p = 0.014; Norway: r = −0.367, p = 0.002). When analysis was focused on the rarest diseases, a stronger correlation exists in all countries (France: r = −0.525, Germany: r = −0.482, Italy: r = −0.497, Spain: r = −0.531, UK: r = −0.436, Sweden: r = −0.455, Norway: r = −0.466; all p < 0.05 except Sweden p = 0.077). Conclusions: This study shows an inverse correlation between annual treatment cost and prevalence with high statistical significance in the studied countries. Although pricing is a complex process where different attributes are assessed, this study supports the idea that payers value rarity in pricing decisions.